Lipoproteins From Bench to Bedside - Kostner, Gerhard; Chennamesetty, Indumathi (IntechOpen, 2015)
In mammalian blood plasma there exist some 6 major lipoprotein classes. Under physiological conditions lipoproteins are certainly beneficial as they transport nutrients and steroids to numerous organs for further metabolism. On the other hand, under pathophysiological conditions most lipoprotein classes promote atherogenesis except of HDL that are considered to be anti-atherogenic. Lipoprotein research is a wide field comprising basic science, analytical methods and clinical investigations. Thus this issue does not raise the claim to give a comprehensive picture of the current knowledge, but rather focuses on specific questions related to animal models in lipoprotein research as well as features of the most atherogenic lipoprotein, Lp(a).